Pelatihan Pembuatan Nata De Soya di Kelurahan Ardirejo Sebagai Pemanfaatan Limbah Cair Olahan Kedelai - Silviyanti Siswoyo, Nurul Amalia; Gema Iftitah A.Y (Universitas 45 Surabaya, 2023)
The soybean processing industry in Indonesia is growing very rapidly. This is because tofu and tempeh products are very popular with the community. Along with the development of industry, industrial waste pollution is also unavoidable. Therefore, it is necessary to innovate the utilization of waste into products that are useful and of high value, one of which is nata de soya. Tempe home industry